P0614URINARY EXOSOMAL MICRORNA-21 AS A MARKER OF SCRUB TYPHUS-ASSOCIATED ACUTE KIDNEY INJURY. (6th June 2020) - Sun, In O; Lee, Kwang Young; Cho, A Young
Abstract: Background and Aims: Urinary microRNA (miRNA)-21 is reported to be a biomarker for detection of acute kidney injury (AKI). Analysis of urinary exsome may serve as a novel diagnostic approach in kidney disease. The aim of this study is to investigate the clinical significance of urinary exosomal miRNA-21 for AKI in patients with scrub typhus. Method: In a cross-sectional study, we collected 138 urine samples at the time of admission from 145 patients with scrub typhus. For 25 patients with scrub typhus-associated AKI and 25 age, sex-matched scrub typhus patient without AKI, we measured miRNA-21 in urinary exosomal fraction and compared diagnostic value in predictiong AKI. Results: Compared with patients in the non-AKI group, patients in the AKI group were more likely to have one or more comorbidity such as diabetes (50% vs. 5%, P<0.01) and chronic kidney disease (8% vs. 0%, P<0.01). Total leukocyte count were higher in patients with AKI than in those without AKI (10.40 × 10 3 / mL vs. 6.40 × 10 3 /mL, P<0.01). The levels of urinary miRNA-21 were higher in the AKI group than in the non-AKI group. Urinary exosomal miRNA-21 levels correlated directly with serum neutrophil gelatinase-associated lipocalin values and total leukocyte counts and inversely with estimated glomerular filtration rate. The receiver operator characteristics curve analysis for urinary exosomal miRNA-21 showed good discriminative power for the diagnosis of scrub typhus-associated AKI, with area under the curve value of 0.907. Conclusion: Urinary exosomal miRNA-21 could be a surrogate markers for the diagnosis of scrub typhus–associated AKI.